Defa'-e Moghaddas (The Sacred Defense), Hamdeli va Mehrvarzi (Camaraderie and Love from Knowing the Other), and the Making of Social Cinema in Post-Revolutionary Islamic Iran - Haghani, Fakhri (Journal of religion and popular culture, 2021)
A publicity tool during the Iran–Iraq war (1980–1988), the cinema of the postwar period in Iran was expected to uphold Islamic, ethical, and symbolic values idealized by the government as defa'-e moghaddas (the sacred defense). The war film genre, which was launched during this period to promote these values, exclusively addressed the presence of men on the front lines. It barely made on-screen references to the role of women. Focusing on the gender dynamics of self-sacrifice and drawing on genres such as drama and melodrama, certain filmmakers used cinemay-e ejtema'i (the social cinema) to translate this ideal to the struggles back home. These films turned the gaze of the camera toward the hidden life of mazlooman (the oppressed). They thus shifted the meaning of defa'-e moghaddas and addressed socio-psychological suffering, oppressive cultural practices ('orf), and unjust sanction of legal codes of qisas (retaliation) as contradictory to Islam's teachings on and cultivation of love, justice, and righteousness among ommat (the Islamic community). Focusing on the Iranian poetic vision of hamdeli va mehrvarzi (camaraderie and love from knowing the other), this essay traces affective states including affinity in struggle, rage, anger, and resistance. Linking instances of these states with Western feminist scholarship on the theory of affect, I discuss the cinematic process of claiming "the right to look" (Mirzoeff, Nicholas, The Right to Look: A Counterhistory of Visuality. Durham, NC: Duke University Press, 2011).